Dairy Enterprise—600 Lactating Cows (Freestall) - Dhuyvetter, Kevin C.; Smith, John F.; Harner III, Joseph P.; Brouk, Micheal (My University, 2006)
This publication describes the production costs and returns for a dairy enterprise with 600 lactating cows in a freestall system.
MF2441_2006_10
Keywords: MF2441; Economics; Livestock; MF